Prospective applications of extracellular vesicle-based therapies in regenerative medicine: implications for the use of dental stem cell-derived extracellular vesicles - Wang, Wenhao; Xu, Zinan; Liu, Minyi; Cai, Mingxiang; Liu, Xiangning (Frontiers in Bioengineering and Biotechnology, 2023)
In the 21st century, research on extracellular vesicles (EVs) has made remarkable advancements. Recently, researchers have uncovered the exceptional biological features of EVs, highlighting their prospective use as therapeutic targets, biomarkers, innovative drug delivery systems, and standalone therapeutic agents. Currently, mesenchymal stem cells stand out as the most potent source of EVs for clinical applications in tissue engineering and regenerative medicine. Owing to their accessibility and capability of undergoing numerous differentiation inductions, dental stem cell-derived EVs (DSC-EVs) offer distinct advantages in the field of tissue regeneration. Nonetheless, it's essential to note that unmodified EVs are currently unsuitable for use in the majority of clinical therapeutic scenarios. Considering the high feasibility of engineering EVs, it is imperative to modify these EVs to facilitate the swift translation of theoretical knowledge into clinical practice. The review succinctly presents the known biotherapeutic effects of odontogenic EVs and the underlying mechanisms. Subsequently, the current state of functional cargo loading for engineered EVs is critically discussed. For enhancing EV targeting and in vivo circulation time, the review highlights cutting-edge engineering solutions that may help overcome key obstacles in the clinical application of EV therapeutics. By presenting innovative concepts and strategies, this review aims to pave the way for the adaptation of DSC-EVs in regenerative medicine within clinical settings.